(untitled) (Rainbow Journal, 2019)
The social sciences comprehend numerous considerations of society and embody a large variety of content drawn from the disciplines of history, geography, politics, economics, and sociology. Social science may be a class of educational disciplines involved with society and therefore the relationships among people inside a society. Social studies demand the inclusion of all students - addressing cultural, linguistic, and learning diversity that has similarities and variations supported race, ethnicity, language, religion, gender, sexual orientation, exceptional learning wants, and different educationally and in-person important characteristics of learners. It’s a rising subject at this time context therefore there’s essential to check on new trends and concepts in social sciences. This study aims to explore the idea of recent trends and concepts of social sciences. This study relies on a review of books, journal articles, and on-line on-the-market secondary sources. This text works as a stepping stone for additional analysis during this field.